Drugs as Chemical Weapons: Past and Perspectives - Vladimír Pitschmann; Zdeněk Hon (Toxics, 2023)
The emergence of modern chemical weapons and chemical warfare is traditionally associated with World War I, but the use of poisons in the military has its roots deep in the past. The sources of these poisons have always been natural agents that also served as medicines. This relationship between poison and medicine, and nowadays between chemical warfare and medicine, or between ‘military chemistry’ and pharmacy, appears to be very important for understanding not only the history but also the possible future of both phenomena. This article looks at some historical examples of the use of drugs as chemical weapons and, conversely, the use of chemical weapons as medicines. It seeks to find answers to some questions that are particularly relevant to the implementation of the Chemical Weapons Convention, which aims to achieve a world without chemical warfare.